By common confession: essays in honor of James M. Renihan - Baines, Ronald S.; Barcellos, Richard C.; Butler, James P.; Renihan, James M. (2015)
"If one were looking for an ambassador for Reformed Baptists in the twenty-first century, there would be few candidates that would match James M. Renihan. To be sure, there are some prominent men, past and present, who are clearly well-known and have been hugely influential in grounding and growing Reformed Baptists from the start.... However, among this wide and diverse body, Dr. Renihan stands as one who has both embraced the movement in its early resurgence, and helped shape and enrich that movement as it has matured. This small volume stands as a tribute to this pastor, theologian, scholar, brother, colleague, and friend from many within the movement and several friends of the movement." - From the back cover